2018
DOI: 10.3390/molecules23040947
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective and Strong Anti-Interference Host-Guest Complex as Fluorescent Probe for Detection of Amantadine by Indicator Displacement Assay

Abstract: Amantadine (AMA) and its derivatives are illicit veterinary drugs that are hard to detect at very low concentrations. Developing a fast, simple and highly sensitive method for the detection of AMA is highly in demand. Here, we designed an anthracyclic compound (ABAM) that binds to a cucurbit[7]uril (CB[7]) host with a high association constant of up to 8.7 × 108 M−1. The host-guest complex was then used as a fluorescent probe for the detection of AMA. Competition by AMA for occupying the cavity of CB[7] allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Also, CB8-encapsulated acridine dye was applied for the fluorescent detection of the peptide drug octreotide in aqueous solution utilizing the competitive host-assisted p K a shift . However, more recently, although IDA-driven sensing of amantadine drug with an anthracyclic-based probe (ABAM) in the presence of CB7 resulted in quenching of the emission of the probe with a recorded LOD of 0.35 nM, the dibucaine drug sensed by quenched emission of berberine, palmatine, and coptisine dyes gave a LOD of 6.0, 12.0, and 25.0 nM, respectively, while emission of the TPPE/CB7 complex enhanced with the addition of methamphetamine drug as a result of aggregate-induced emission produced a LOD of only 0.43 μM . Furthermore, Alzheimer disease drug “memantine” was sensed in the blood serum through the IDA mechanism with [2.2]­paracyclophane-derivative-indicator dyes and CB8 as a macrocycle .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, CB8-encapsulated acridine dye was applied for the fluorescent detection of the peptide drug octreotide in aqueous solution utilizing the competitive host-assisted p K a shift . However, more recently, although IDA-driven sensing of amantadine drug with an anthracyclic-based probe (ABAM) in the presence of CB7 resulted in quenching of the emission of the probe with a recorded LOD of 0.35 nM, the dibucaine drug sensed by quenched emission of berberine, palmatine, and coptisine dyes gave a LOD of 6.0, 12.0, and 25.0 nM, respectively, while emission of the TPPE/CB7 complex enhanced with the addition of methamphetamine drug as a result of aggregate-induced emission produced a LOD of only 0.43 μM . Furthermore, Alzheimer disease drug “memantine” was sensed in the blood serum through the IDA mechanism with [2.2]­paracyclophane-derivative-indicator dyes and CB8 as a macrocycle .…”
Section: Resultsmentioning
confidence: 99%
“…The employment of cucurbit­[ n ]­urils (CBs) to tweak fluorescence signals utilizing the IDA strategy is well-known for detection of spectroscopically (optically) silent drug molecules. The reported sensing strategies in these examples were conceivably dependent on numerous processes, such as the host-assisted interactions between aromatic rings, the host-assisted aggregation-induced emission (AIE), or the dye deaggregation upon complexation . The utilization of other beneficial chemical equilibria and photochemical processes, which lead to the generation of fluorescent sensors that are highly sensitive to the analyte, has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…62,63 Thus, amantadine concentration of $40 mM will be found for up to 24 h in urine. Following established routines for spectroscopic urine diagnostics, 19,20,64 urine samples were diluted with water in a 1 : 4 ratio in order to reduce the absorbance of real urine and to avoid inner lter effects. As the analyte concentration in urine samples is usually unknown, we devised a new method for using chemosensor 1 for quantifying amantadine in real urine samples.…”
Section: Edge Articlementioning
confidence: 99%
“…Therefore, many reported CBn-based chemosensors are operational for sensing applications in deionized water or "minimal buffers" but were oen not suitable for applications in saline media or biouids, especially if their salt concentration is varying from sample to sample (matrix effects). 19,20 We recently demonstrated that the use of a high-affinity dye for CB8 enabled the detection of the drug memantine in blood serum by IDA. 21 However, this approach can have severe fundamental limitations, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, radioenzyme immunoassay utilizes radioactive adenosine, which can cause pollution and require expensive antibody costs. The instrumental analysis has some inevitable limitations such as tedious sample pretreatment, complicated chemical modification, precise instruments, long analysis time and low sensitivity [25]. Compared with the above analytical methods, the fluorescence probe method has attracted extensive concern owing to its rapidness, simplicity, high sensitivity, good stability, and low cost.…”
Section: Introductionmentioning
confidence: 99%